Electrochemical sensing of dopamine and pyrogallol on mixedanalogue of Prussian blue nanoparticles modified electrodes Role oftransition metal on the electrocatalysis and peroxidasemimetic activity - Pandey P.C.; Pandey A.K. (My University, 2025)
The electrochemical sensing of dopamine and pyrogallol using mixed copper-iron hexacyanoferrate(Cu-FeHCF) nanodispersion is investigated to understand the dependence of the same on heterotransition-metal ions. We also investigated that Prussian blue and its mixed metal analogues of Mn,Ni and Cu (i.e. Mn-FeHCF, Ni-FeHCF and Cu-FeHCF) possess intrinsic peroxidase like activity capable ofcatalyzing the oxidation of dopamine (DA) and pyrogallol (Py) by H2O2. The relative variation in catalyticactivity based on both electrochemical and spectroscopic measurements of FeHCF, Mn-FeHCF, Ni-FeHCFand Cu-FeHCF nanoparticles is examined for DA sensing and found in the order of: Cu-FeHCF > Mn-FeHCF > Ni-FeHCF > FeHCF. Furthermore, the electrocatalytic activity of Cu-FeHCF towards the DA and Pyis also examined based on differential pulse voltammetry. In addition to that, the Cu-FeHCF nanomaterialexhibits excellent electrocatalytic activity with the catalytic rate constant to the order of 1.05 × 102and2.34 × 102M -1s-1for DA and Py respectively reflecting the introduction of differential electrocatalyticactivity as a function of analytes (DA and Py). © 2013 Elsevier Ltd. All rights reserved.